STUDY VISITS - CONNECTIONS WITH THE LABOR MARKET, A STUDY IN ROMANIA - Elisabeta SPUNEI; Nătălița-Mihaela FRUMUȘANU; Mihaela MARTIN (Universitaria Publishing House, Craiova, 2024)
This paper presents a case study based on student's responses to a survey applied in an extracurricular project carried out in 2022, who have made study visits, as an extracurricular activity, to present their role for labour market integration. Through extracurricular projects, including study visits, students can discover new equipment and technologies used in companies and identify the workflow at different workplaces. Study visits provide students with the opportunity to gain a real-time perspective on the field they aspire to work in and connect with professionals in that domain, establishing direct contact with various departments and functions within an organization. The study highlights the need to identify students' preferences so that activities carried out throughout the years of study respond as best as possible to their needs.